The Effect of Heavy Metal Treatments on Uptake of Nitrogen, Phosphorus and Potassium in Transgenic and Non-Transgenic Tobacco Plants - Hatice Dağhan (Journal of Agricultural Sciences)
Heavy metals affect nutrient uptake of plants by means of either effecting root development and transport systems or interfering with other plant nutrients in soil solution. In this study, the effect of toxic levels of copper (Cu), zinc (Zn), cadmium (Cd), and nickel (Ni) on the uptake of nitrogen (N), phosphorus (P) and potassium (K) were investigated in hydroponic culture. There was no toxicity sign in 5 mg Zn L-1 level but the rest of the heavy metals used caused different extent of toxicity. The first visual signs of toxicity for these heavy metals were chlorosis and the reduction in shoot and root biomass due to inhibition of metabolic functions. As a result, N, P, K uptake significantly changed. As the ratio of percent decreases for N, P, K uptake were considered, the toxicity levels of the heavy metals were, in descending order, Ni > Cu > Zn > Cd. Ni had the element that having most serious inhibition effect on the concentration of all three elements, the order of other heavy metals were determined as Cu > Zn > Cd for P and Cu > Cd > Zn for K.